2019
DOI: 10.2147/ccid.s186621
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical and instrumental evaluation of a new topical non-corticosteroid antifungal/anti-inflammatory/antiseborrheic combination cream for the treatment of mild-to-moderate facial seborrheic dermatitis</p>

Abstract: PurposeTopical agents play a key role in the management of facial seborrheic dermatitis (SD) by reducing inflammation and scale production. The aim of this open-label trial was to assess the efficacy and tolerability of a new non-corticosteroid, antifungal/anti-inflammatory/antiseborrheic cream containing piroctone olamine, stearyl glycyrrhetinate, and zinc PCA in the treatment of facial SD using clinical and instrumental evaluation.Patients and methodsTwenty adult subjects affected by mild-to-moderate inflame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Moreover, an important improvement efficacy for both face and chest in terms of IGA score was reported for all patients reaching a mild response at W1 (mean IGA score: 4.75 for face and 3.75 for chest) and excellent response at W2 (mean IGA score: 9.4 for face and 8.1 for chest). All these data are supported by Micali et al In fact, they have previously evaluated IGA score after 8 weeks of NSC treatment, reporting good and excellent responses in 29.5% and 53% of patients, respectively [26]. Beyond the clinical efficacy, here we have also deepened the antifungal property in vivo, based on previous evidence in which this characteristic of NSC had already been tested in an ex vivo model [27].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, an important improvement efficacy for both face and chest in terms of IGA score was reported for all patients reaching a mild response at W1 (mean IGA score: 4.75 for face and 3.75 for chest) and excellent response at W2 (mean IGA score: 9.4 for face and 8.1 for chest). All these data are supported by Micali et al In fact, they have previously evaluated IGA score after 8 weeks of NSC treatment, reporting good and excellent responses in 29.5% and 53% of patients, respectively [26]. Beyond the clinical efficacy, here we have also deepened the antifungal property in vivo, based on previous evidence in which this characteristic of NSC had already been tested in an ex vivo model [27].…”
Section: Discussionsupporting
confidence: 74%
“…Our findings are in line with a recent study that reported NSC clinical efficacy up to 8 weeks, with a significant reduction of erythema, pruritus and desquamation. In particular, they observed a 90% reduction of VAS pruritus in the facial area, reporting 0.67 ± 1.05 cm after 2 weeks of NSC, with respect to 6.9 ± 1.68 cm at baseline [26]. Here, we observed an 85% reduction of VAS pruritus in the facial area, reporting 1.5 ± 0.70 cm after 2 weeks of NSC treatment with respect to 9.6 ± 0.14 cm at baseline.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, the efficacy of the novel NSFC tested in this study is supported by results from clinical trials. Here, NSFC demonstrated significant effects on desquamation, erythema, and pruritus in subjects with mild-to-moderately inflamed facial SEBD [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 10–12 have assessed this topical treatment in populations without HIV, but this case series provides specific information on the HIV-positive population group, which can be resistant to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In SD patients without HIV, various publications have shown the usefulness of a non-steroidal, antifungal, anti-inflammatory and antiseborrheic cream marketed under the name Nutradeica (ISDIN, Spain). 10–12 This combines several ingredients including piroctone olamine, which has antifungal properties; 10 , 13 the zinc salt of l-pyrrolidone carboxylate (zinc PCA), which has antifungal and anti-inflammatory properties; biosaccharide gum-2, which has anti-inflammatory and antifungal properties; and stearyl glycyrrhetinate, which has anti-inflammatory, antioxidant, and skin-soothing properties. 14 This topical treatment has previously been reported to accelerate recovery and prevent flare-ups.…”
Section: Introductionmentioning
confidence: 99%